Multidimensional approach usefulness in early Alzheimer’s disease: Advances in clinical practice - Pruneti, Carlo; Innocenti, Augusto; Cammisuli, Davide Maria (Acta Biomedica Atenei Parmensis, 2018)
Background and aim: Improving quality of life of patients with early Alzheimer’s Disease (AD) is a primary concern of health professionals involved in dementia treatment. The aim of this study is to reveal associations among psychiatric symptoms and wellbeing aspects, dysfunctional lifestyles and stress-related behaviors, illness perception, personality traits, and life quality satisfaction, in order to offer a comprehensive evaluation of psychological and behavioral aspects characterizing patients with early AD. Methods: This is a cross-sectional study in which all the outpatients included were evaluated at the Dementia Clinic in Parma (Italy). 21 patients with probable AD were assessed by an overall cognitive screening (Milan Overall Dementia Assessment), the evaluation of personal and instrumental autonomy (Activities of Daily Living and Instrumental Activities of Daily Living), and of dementia severity (Clinical Dementia Rating Scale). After the neurocognitive assessment, a wide battery of clinical and psychological measures (Symptom Questionnaire, Pisa Stress Questionnaire, Illness Behavior Questionnaire, Sixteen Personality Factor Questionnaire and Satisfaction Profile) was administered to the patients. Spearman’s rho correlations between clinical and psychological measures were performed. Results: A tendency to deny anxiety, depressive and somatic symptoms might be present in patients with early AD. They also present with hypochondriasis, resulting in higher level of anxiety and depression. Reduced liveliness and self-reliance as personality traits may influence the intensity of such symptoms. Conclusions: A comprehensive assessment including psychological and clinical measures should be routinely integrated in clinical practice for the evaluation of patients with early AD.